Novel poly(hydroxyalkanoates)-based composites containing Bioglass® and calcium sulfate for bone tissue engineering - García-García, Jose; Garrido, Leoncio; Quijada-Garrido, Isabel; Kaschta, Joachim; Schubert, Dirk W.; Boccaccini, Aldo R. (Biomedical Materials, 2012)
Three different poly(hydroxyalkanoates) (PHAs), copolymers of poly(3-hydroxybutyrate) (P3HB), have been used to make composites using two different fillers, bioactive glass (type 45S5 Bioglass®) and calcium sulfate dihydrate. The PHAs used were poly(3-hydroxybutyrate-co-3-hydroxyvalerate) [PHBHV] and two copolymers of poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) [PHBHHx]. The aim of the study was the fabrication and characterization of the new composites and the assessment of the influence of the particular filler combination on the physical properties and bioactivity of the films. The thermal behaviour was studied using differential scanning calorimetry while mechanical properties were evaluated using dynamic mechanic thermal analysis and tensile strength test. The mechanical and thermal properties were affected by particles addition. The distribution of the particles in the polymer matrix, observed by scanning electron microscopy, was directly related to the mechanical properties. The surface characteristics were investigated by contact angle measurements and Raman spectroscopy. The extent of formation of hydroxyapatite (HA) upon immersion in simulated body fluid (SBF) depended on the polymer used, the amount of fillers employed and the time of immersion in SBF. Bioactivity was enhanced in the composites with a rise of hydrophilicity. The HA formation was controllable with time in the case of PHBHHx composites.
UnivIS-Import:2015-03-09:Pub.2012.tech.IW.LM.novelp